Isomerization of C5-C7 linear alkanes over WO3-ZRO2 under helium atmosphere - Triwahyono, Sugeng (Penerbit UTM Press, 2015)
The effect of WO3 on the properties and catalytic isomerization of C5-C7 linear alkanes over ZrO2 was studied under helium atmosphere. The WO3-ZrO2 was prepared by impregnation of Zr(OH)4 with an aqueous (NH4)6[H2W12O40], followed by calcination at 1093 K for 3 h in air. The amount WO3 was 10 wt%. XRD and BET studies showed that the introduction of WO3 stabilizes the tetragonal phase of ZrO2, leading to larger surface area and stronger acidity of ZrO2. Pyridine FTIR study verified the interaction of WO3 with ZrO2 formed strong Lewis and Bronsted acid sites. The presence of WO3 increased the catalytic isomerization of C5-C7 linear alkanes. The conversion of C5, C6 and C7 reached 1.3, 2.6 and 5.1 %, respectively. While the selectivity of isopentane, isohexane and isoheptane reached 15.6, 20.5 and 19.5 %, respectively. The high activity of WO3-ZrO2 was due to the ability of WO3 to adsorb and dissociate linear alkane to form hydrogen and alkane radical in which the atomic hydrogen underwent to the formation of protonic acid sites and hydride. The presence of protonic acid sites and hydride determined the activity of WO3-ZrO2